2009
DOI: 10.1139/y09-112
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3E treatment regulates matrix metalloproteinases and prevents vascular reactivity alterations in diabetic rat aortaThis article is one of a selection of papers published in a special issue on Advances in Cardiovascular Research.

Abstract: It is known that increased generation of oxidants and (or) reduced endogenous antioxidant defense mechanisms are associated with the etiology of diabetic vascular complications. Although a close correlation exists between increased oxidative stress and the activation of matrix metalloproteinases (MMPs), little is known about the effect of hyperglycemia on the regulation and contribution of MMPs in the vascular system. Therefore, we aimed to examine whether omega-3E (50 mg/kg per day for 4 weeks), a long-chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…As illustrated in Figure 1F, the maximal responses to Phe-precontraction in the either diabetic group or control group in the presence of L-NAME are not significantly different from those of absence of L-NAME. Our first data with diabetics can provide a first information related with diabetes-induced a contractile vascular function, of which showed, that contractions in response to phenylephrine were not effected from NO-release in diabetic rat aortic rings [14,15,18]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As illustrated in Figure 1F, the maximal responses to Phe-precontraction in the either diabetic group or control group in the presence of L-NAME are not significantly different from those of absence of L-NAME. Our first data with diabetics can provide a first information related with diabetes-induced a contractile vascular function, of which showed, that contractions in response to phenylephrine were not effected from NO-release in diabetic rat aortic rings [14,15,18]. …”
Section: Resultsmentioning
confidence: 99%
“…Although many studies were performed with several animal models, there are conflicts related with the vascular responses to contractile agents in the diabetic subjects. Accordingly, some studies suggested increased sensitivity to noradrenaline [28], whereas other studies, including our team’s studies, reported an attenuated contractile response to noradrenaline in the aortas from diabetic animals [14,15,18,29]. These studies mainly stated that the impaired contractile responses to phenylephrine applications could be due to a change in α-adrenergic receptor expression in the vasculature [30].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The activity of MMPs like MMP-2, -3, and -9 are reported to be regulated by long chain polyunsaturated fatty acids (LCPUFA) [17][19]. Our earlier studies in preterm deliveries indicate increased oxidative stress and reduced LCPUFA especially docosahexaenoic acid (DHA) levels in preterm pregnancy [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported increased placental levels of MMP1 (collagenase) and MMP9 (gelatinase) in women delivering preterm (Sundrani et al 2012). The activity of MMPs is reported to be regulated by homocysteine, oxidative stress, and long-chain polyunsaturated fatty acids (LCPUFA; Guo et al 2006, Kundu et al 2009, Solakivi et al 2009, Zainal et al 2009, Zeydanli & Turan 2009, Ke et al 2010.…”
Section: Introductionmentioning
confidence: 99%